2011
DOI: 10.1111/j.1740-0929.2010.00862.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary inclusion of sorghum milling waste on growth response, nutrient utilisation, gut characteristics and cecal microflora of weaner rabbits

Abstract: Growth response, nutrient digestibility and cecal microflora of 80 male, mixed breed weaner rabbits fed with varying dietary inclusions of sorghum milling waste (SMW) was investigated. Four experimental diets were formulated such that SMW was included at 0 (control), 100, 200 and 300 g/kg, respectively. Each dietary treatment was performed on 20 rabbits. Feed intake increased (P < 0.05) while final live weight and feed conversion ratio of rabbits decreased (P < 0.05) following increased dietary inclusion of SM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…Fish generally require omega-3 fatty acids rather than omega-6 fatty acids in contrast to terrestrial animals which require omega-6 fatty acids [19] . Previous works of Oso et al, [20] showed the need to use plant meal in combined form to produce the cheapest and required nutrient for fish and this formed the basis of this research work. The crude proteins from the five diets are within the requirements recommended for catfish C. gariepinus fingerlings in tropics which agreed with the work of Oso et al; Eyo and Falayi [20,21] .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Fish generally require omega-3 fatty acids rather than omega-6 fatty acids in contrast to terrestrial animals which require omega-6 fatty acids [19] . Previous works of Oso et al, [20] showed the need to use plant meal in combined form to produce the cheapest and required nutrient for fish and this formed the basis of this research work. The crude proteins from the five diets are within the requirements recommended for catfish C. gariepinus fingerlings in tropics which agreed with the work of Oso et al; Eyo and Falayi [20,21] .…”
Section: Discussionmentioning
confidence: 93%
“…Previous works of Oso et al, [20] showed the need to use plant meal in combined form to produce the cheapest and required nutrient for fish and this formed the basis of this research work. The crude proteins from the five diets are within the requirements recommended for catfish C. gariepinus fingerlings in tropics which agreed with the work of Oso et al; Eyo and Falayi [20,21] . The results obtained in these studies agreed with Fasakin et al; Ugwumba, et al, [22,23] that relatively low fibres and high protein contents as revealed in the fish growth and better utilization by fish growth and feed conversion ratio in this studies.…”
Section: Discussionmentioning
confidence: 93%
“…At 56th day of the study, three birds per pen ( n = 18 per treatment) were selected and slaughtered for the collection of caecal content. Fresh samples of caecal contents ( n = 18 per treatment) obtained were used for the estimation of gut microbiota (Oso et al., ). A gram sample was dispersed in 9 ml phosphate‐buffered saline solution supplemented with 0.5 g/l cysteine‐hydrochloride, and further diluted to a factor of 10 −8 .…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, rabbits fed Phaseolus vulgaris straw (PS) containing various additives showed lower coliform count in their caecal content when compared with those fed the clover hay diet's (El-Gohary & Abo El-Maaty, 2014). On the other hand, Oso et al (2011), who recorded that lower microbial counts in caecal contents of rabbits fed with 300 g/kg sorghum milling waste which could indicate the increased digesta transient rate caused by high dietary fiber.…”
Section: Effects Of Dietary Sbt Levelmentioning
confidence: 99%